Analisis Tenaga Kerja dalam Meningkatkan Produktivitas Pekerjaan pada Pembangunan Perumahan Palm Vista Residence - Naimatul Fikriyah; Kartono Wibowo; Abdul Rochim (JURAL RISET RUMPUN ILMU TEKNIK, 2026)
Labor productivity is a critical factor in construction project success as it directly affects time, cost, and work quality. In the Palm Vista Residence housing development project, delays in ground floor structural works indicate suboptimal human resource performance. This study aims to analyze labor productivity levels, identify factors influencing productivity, and formulate strategies to improve productivity in sloof beams, columns, and floor slab works. The research employs a quantitative approach with descriptive-analytical methods through field observations, questionnaires, and interviews. Labor productivity is measured using the work sampling method and the Labour Utilization Rate (LUR), while influencing factors are analyzed using multiple linear regression. Strategy prioritization for productivity improvement is determined using the Analytical Hierarchy Process (AHP). The results show that labor productivity is at a moderate level and is significantly influenced by work experience, managerial aspects, and coordination and planning. The priority strategies include improving worker competence and strengthening project management practices. These findings are expected to provide practical guidance for construction labor management to enhance efficiency and ensure timely project completion.